Cost-effectiveness of telehealthcare to patients with chronic obstructive pulmonary disease: results from the Danish ‘TeleCare North’ cluster-randomised trial - Witt Udsen, Flemming (BMJ Open, 2017)
OBJECTIVES: To investigate the cost-effectiveness of a telehealthcare solution in addition to usual care compared with usual care. DESIGN: A 12-month cost-utility analysis conducted alongside a cluster-randomised trial. SETTING: Community-based setting in the geographical area of North Denmark Region in Denmark. PARTICIPANTS: 26 municipality districts define randomisation clusters with 13 districts in each arm. 1225 patients with chronic obstructive pulmonary disease were enrolled, of which 578 patients were randomised to telehealthcare and 647 to usual care. INTERVENTIONS: In addition to usual care, patients in the intervention group received a set of telehealthcare equipment and were monitored by a municipality-based healthcare team. Patients in the control group received usual care. MAIN OUTCOME MEASURE: Incremental costs per quality-adjusted life-years gained from baseline up to 12 months follow-up. RESULTS: From a healthcare and social sector perspective, the adjusted mean difference in total costs between telehealthcare and usual care was €728 (95% CI −754 to 2211) and the adjusted mean difference in quality-adjusted life-years gained was 0.0132 (95% CI −0.0083 to 0.0346). The incremental cost-effectiveness ratio was €55 327 per quality-adjusted life-year gained. Decision-makers should be willing to pay more than €55 000 to achieve a probability of cost-effectiveness >50%. This conclusion is robust to changes in the definition of hospital contacts and reduced intervention costs. Only in the most optimistic scenario combining the effects of all sensitivity analyses, does the incremental cost-effectiveness ratio fall below the UK thresholds values (€21 068 per quality-adjusted life-year). CONCLUSIONS: Telehealthcare is unlikely to be a cost-effective addition to usual care, if it is offered to all patients with chronic obstructive pulmonary disease and if the willingness-to-pay threshold values from the National Institute for Health and Care Excellence are applied. TRIAL REGISTRATION: Clinicaltrials.gov, NCT01984840, 14 November 2013.